Escuela rural: análisis bibliométrico internacional (2015-2019) - Carmen Álvarez-Álvarez; Francisco Javier García-Prieto (Universidade Federal do Norte do Tocantins, 2021)
There are rural schools in all countries, with peculiarities that make them unique, while sharing substantive aspects. We present a bibliometric study in which 32 studies on rural school in the period 2015-2019 taken from the Web of Science and Scopus are analyzed. They have been filtered based on some parameters and analyzed according to these indicators: impact, subject matter, territory, objective, type of study, research techniques, subjects, type of school, results, conclusions and limitations. The results show that local, qualitative studies predominate, focused on curricular issues and developed with teachers. It is necessary to have studies published in the first quartiles, to use more than one data collection technique, to mention the characteristics of rural schools, to bet on large samples and to avoid accessory studies.